Time to listen to children : personal and professional communication - Milner, Pat, 1936-; Carolin, Birgit, 1933- (Routledge, 1999)
This practical guide to communicating with children stresses the importance of learning to listen. Contributors give accounts of their work in education, social services, health, law and voluntary organizations.